Plasmonic and nonlinear optical behavior of nanostructures in glass matrix for photonics application. (May 2020) - Kumar, Promod; Chandra Mathpal, Mohan; Prakash, Jai; Jagannath, Gangareddy; Roos, WD; Swart, H.C.
Graphical abstract: Schematic diagram depicting Ag/Cu core - shell nanostructures in glass. Highlights: Ag/Cu core shell nanostructures were formed in glass by ion exchange technique. Core shell nanostructures were confirmed from TEM results. Nonlinear optical properties were investigated using Z-scan technique. These core shell nanostructures are beneficial for photonic applications. Abstract: There is a growing interest in bimetallic core shell nanostructures that comprised out of noble metals due to their fascinating plasmonic properties, leading to a wide range of applications in future nanotechnology. Here we report on Ag/Cu core shell nanostructures in a glass matrix. It includes novel approaches for characterizing embedded core shell nanostructures with a detailed study on the nanosize effect in tuning their optical and nonlinear optical properties along with biomedical applications. Annealing the Ag/Cu as- exchanged samples resulted in the formation of core-shell nanostructures, which were confirmed using UV–vis absorption spectroscopy and high-resolution transmission electron microscopy. The prepared plasmonic nanostructures were further studied using X-ray diffraction, Rutherford backscattering, photoluminescence, Raman, X-ray photoelectron spectroscopy and Z scan techniques. The nonlinear optical properties of the glasses containing bimetallic nanoparticles have been studied at a non-resonant wavelength using femtosecond laser pulses and a possible mechanism for the observed nonlinearity have been explained.